ARTERIAL HYPERTENSION ASSOCIATED WITH METABOLIC SYNDROME: FOCUS ON DAILY PROFILES OF CENTRAL AORTIC PRESSURE AND VASCULAR STIFFNESS - L. A. Panchenkova; L. A. Andreeva; K. A. Khamidova; T. E. Yurkova; A. I. Martynov (Евразийский Кардиологический Журнал, 2016)
Purpose: to evaluate the parameters of the central aortic pressure and arterial stiffness during the day in patients with arterial hypertension (AH) with metabolic syndrome (MS) Material and methods: The study included 48 subjects divided into 2 groups: 23 (47,9%) subjects with AH, 25 (52,1%) subjects with AH with MS (AH+MS). Control group (CG) were 22 practically healthy subjects. All the subjects underwent examination ABPM with oscillometric sensor (BPLabVasotens, Russia) with assessment CAP (systolic blood pressure, SBPao; diastolic blood pressure DBPao; pulse pressure,PPao; Augmentation index, Alxao; amplification of pulse pressure, PPA) and arterial stiffness (pulse wave velocity, PWVao; Reflected Wave Transit Time, RWTT; Arterial Stiffness Index, ASI; Augmentation index, AIx). Results: Analysis of CAP demonstrated significant differences between the day / night SBP ao, DBP ao., mean BP ao in AH and AH + MS groups compared to the CG. No significant differences in the parameters of pulse pressure (PP) during the day in these groups are not mentioned, but PP is higher in AH + MS group. Augmentation Index for 24 hours significantly higher, amplification of pulse pressure was significantly lower in the AH + MS compared to CG and AH group. Evaluation of daily arterial stiffness parameters revealed significantly higher rates in PWVao in AH + MS group comparison with the CG and AH group. RWTT statisticaly significant lower in AH + MS and AH groups compared to CG. Conclusion: 24-hour monitoring of CAP and AS revealed a deterioration of the elastic properties of central arteries in hypertensive subjects with metabolic syndrome. Thus, the results of our study confirm the importance of the study of arterial stiffness and the CAP and in the long term could be considered as markers in hypertensive patients, especially in the presence of comorbid pathology.